Hubungan Kadar Hemoglobin dan Status Gizi Dengan Kebugaran Jasmani Remaja di SMK Negeri 47 Jakarta - Azkiya, Rahmi; Harjatmo, Titus Priyo; Karina, Sa’diah Multi; Soekatri, Moesijanti (JGK: Jurnal Gizi dan Kesehatan, 2024)
Physical fitness is a person's body's ability to carry out daily tasks without fatigue. Physical fitness is very important, especially in teenagers because they have a lot of activities. After Covid-19, several studies have shown that fitness in teenagers is decreasing. This can be influenced by several factors, including hemoglobin levels in the blood and nutritional status. The aim of this research was to determine the relationship between hemoglobin levels and nutritional status and the body fitness of teenagers at public vocational school 47 Jakarta. This research was conducted with a cross sectional research design. Samples were taken by purposive sampling that met the inclusion and exclusion criteria. Data collection includes gender, age, hemoglobin levels using the For a 6 Plus digital tool, nutritional status, and fitness level using the Shuttle Run Test. Data analysis included frequency and bivariate distribution using Fisher's exact test. The research results showed that most of the respondents, 75.5% were female, 62% were 16 years old, 61.4% had very weak fitness levels, 52.1% had normal Hb levels, and 69.9% had normal nutritional status. There is a significant relationship between hemoglobin levels and physical fitness (p=0.034) and there is a significant relationship between nutritional status and physical fitness (p=0.001).